The double-edged role of SPAG6 in male reproductive toxicity: pro-invasive in leukemia, protective in germ cells - Jing Luo; Jiaxiu Yin; Junli Mou; Kexin Lin; Lin Liu; Yao Zhang (Frontiers in Medicine, 2026)
Background Male testis is highly susceptible to irreversible damage from acute myeloid leukemia (AML) infiltration and subsequent chemotherapy. As a gene critical for sperm function, the role of SPAG6 in AML testicular infiltration and chemotherapy-induced injury remains poorly elucidated. Methods SPAG6 expression was knocked down in C1498 leukemia cell line, and its impact on testicular infiltration was evaluated in vivo . RNA sequencing was performed to identify altered pathways. In parallel, SPAG6 was silenced in murine GC-1 spg spermatogonial cells, followed by assessment of reactive oxygen species (ROS) levels and cell proliferation. Results Both AML infiltration and subsequent chemotherapy exerted profound damage on the testes. SPAG6 was highly expressed in normal mouse testes and was upregulated upon AML infiltration and chemotherapy. Knockdown of SPAG6 in leukemia cells was associated with suppressed proliferation and induced apoptosis in vitro , and reduced testicular infiltration in vivo ; chemotherapy further enhanced these effects. RNA sequencing and wound healing assay further indicated that SPAG6 depletion may impair cell adhesion and migration. Conversely, silencing SPAG6 in spermatogonial cells was linked to suppressed proliferation, elevated mitochondrial membrane potential and ROS levels, and these effects were further exacerbated under chemotherapeutic challenge. Conclusion SPAG6 may exert cell-type-specific, opposing roles in AML-infiltrated testes: SPAG6 depletion is associated with suppressed leukemic cell infiltration, potentially through modulation of cell adhesion, while its deficiency correlates with increased chemotherapy-induced injury to spermatogonial cells.